IMPROVING STUDENTS' WRITING SKILLS THROUGH FIELD TRIP METHOD - Risa Meiranti (English Review: Journal of English Education, 2012)
Abstract: This research is aimed to improve the students’ writing skill and learning activity by applying the implementation of field trip method in English subject in class VIII-2 SMP N 1 Luragung. The problem in this research contents is about the low of students’ skill in writing and learning activity. The kind of this research is classroom action research which was conducted in two cycles. The subject of this research is English subject in class VIII-2 with total number of students 34. The research instrument that had been used is the test and also the observation sheet for observation the learning activity of the students and teacher. Based on the result, the improvement could be seen from the increase of students’ mean writing score from 47 in the preliminary study and 70,51 at the first cycle  to 73,24 in the second cycle. The result of field notes showed that the class condition during teaching learning process creates the positive atmosphere in the classroom and makes students creative in finding the ideas, organize the text and can use better grammar. Students who had been afraid of learning in the second cycle looked more confident. Students in the second cycle was more confident in working task of the students and students’ participation in learning increased, they actively asked, answered questions from teacher. Keyword: writing skill, field trip method, improvement, action research